Análise eletromiográfica da musculatura supra- hióidea pré e pós uso de bandagem elástica em mulheres jovens - Gomez, Yulieth Paulina Stave (2021)
The aim of this research was to compare the effects of an exclusive Tounge Coupling exercise, and its association with the MTT® elastic bandage on the suprahyoid muscles of young women. This is a prospective, quantitative and experimental research, which include 14 women such as sample, between 19 and 25 years old (average of 24.1 years old). AMIOFE-E protocol complemented with the MGBR protocol was used to speech-language clinical evaluation, the structural analysis of tonus and resting tongue posture. The swallowing test was used to evaluate of functional aspect. In addition, the signal of the electrical activity of the suprahyoid muscles was captured during resting situation, maximum voluntary contraction and swallowing of liquid pre and post intervention. Finally, the electrical activity of the suprahyoid muscles during the tongue coupling was recorded during15 seconds to obtain a parameter for recording the pre- therapeutic condition of the participants. Miotool equipment of eight channel was used to electromyographic examination. The intervention was distributed using randomization, to the participants allocating them in two proposals. The Experimental Group performed muscle training of three series three times a day, tounge coupling for 15 seconds during a week, associated with the use of the Therapy Taping®, bandage without tension, on the suprahyoid muscles, while the Control Group performed only the muscle training of tongue coupling. For the result analysis, the Shapiro Wilk Test was applied to investigate normality of data obtained. In the same way, Student's T tests, Wilcoxon Test, U-Mann-Whitney Test and Friedman's ANOVA tests used, all considering a significance level of 5% for all tests. Because of this study, no statistically significant differences were found in the myoelectric activity of the suprahyoid muscles in the comparison of the pre and post intervention values in situations of rest, deglutition and maximum voluntary contraction, in both groups and between them. In addition, the application of elastic bandage without tension did not generate variability in the results, due to the responses in both groups were similar. In relation to the values of the electrical activity during the training, carried out before and after last week, statistical significance was not observed. Regarding the assessment of the bandage, perception, through the questionnaire of appreciation of the method, was evidenced that the participants perceive modifications and positive impressions in relation to the use of the bandage. At the end of the treatment, the members of the experimental group will indicate improvement in the perceptions of the study region. The results of this research will allow concluding that this improvement proposal, for this target population, did not have an effect on muscular electrical activity, but rather positive qualitative results in relation to the perception of the stimulated area.